2021
DOI: 10.3390/bioengineering8010011
|View full text |Cite
|
Sign up to set email alerts
|

Extending In-Plane Impedance Measurements from 2D to 3D Cultures: Design Considerations

Abstract: Three-dimensional (3D) cell cultures have recently emerged as tools for biologically modelling the human body. As 3D models make their way into laboratories there is a need to develop characterisation techniques that are sensitive enough to monitor the cells in real time and without the need for chemical labels. Impedance spectroscopy has been shown to address both of these challenges, but there has been little research into the full impedance spectrum and how the different components of the system affect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The authors suggested this may be due to an increase in conductivity that occurs as the culture medium hydrates the gel; notably though, this effect was less pronounced in hydrogels embedded with stromal cells, which were presumed to act as insulators against the current. Conversely, De Leon et al , using a planar electrode configuration, found that impedance of collagen gel increased with time over a range of 112 Hz to 31.2 kHz, which they attributed to protein and macromolecule deposition onto the electrodes 16 . The use of PM-ECIS, which measures cells directly grown on the electrodes, and is robust to the presence of hydrogel in other compartments ( Figure C ), circumvents these issues.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The authors suggested this may be due to an increase in conductivity that occurs as the culture medium hydrates the gel; notably though, this effect was less pronounced in hydrogels embedded with stromal cells, which were presumed to act as insulators against the current. Conversely, De Leon et al , using a planar electrode configuration, found that impedance of collagen gel increased with time over a range of 112 Hz to 31.2 kHz, which they attributed to protein and macromolecule deposition onto the electrodes 16 . The use of PM-ECIS, which measures cells directly grown on the electrodes, and is robust to the presence of hydrogel in other compartments ( Figure C ), circumvents these issues.…”
Section: Discussionmentioning
confidence: 98%
“…The geometries of microfluidic devices exacerbate the non-homogenous current distribution inherent to this technique, with TEER measurements in microfluidic devices tending to be of greater magnitude than in cell culture inserts 7 . Even with the use of geometric correction factors 4,5 , however, simple subtraction of the hydrogel devices fails to take into account the cell distribution and behaviours that may induce changes in the hydrogel, as well as the inherent stability of the matrix 16 . Indeed, there is evidence to suggest that hydrogel contribution to impedance itself changes over time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…272 Many OOC setups employ the use of biomaterials like hydrogels and co-culture with support cells, and simply subtracting hydrogel-only TEER values from cell culture devices does not take into account the effect of cell distribution and behaviours, nor the inherent stability of the matrix on the hydrogel's electrical properties. 273,274 Finally, common practices of reporting TEER, impedance spectroscopy and ECIS outputs as normalized values can mask flaws in the raw data, as well as making it difficult to compare results across publications. 178…”
Section: Lab On a Chip Critical Reviewmentioning
confidence: 99%